Exterranean : extraction in the humanist Anthropocene - Usher, Phillip John (Fordham University Press, 2019)
Exterranean concerns the extraction of stuff from the Earth, a process in which matter goes from being sub- to exterranean. By shifting emphasis from emission to extraction, Usher reorients our perspective away from Earthrise-like globes and shows what is gained by opening the planet to depths within. Both historicist and speculative in approach, Exterranean eschews the self-congratulatory claims of posthumanism and lays the groundwork for a comparative ecocriticism that reaches across periods and languages.
Keywords: Ecocriticism.; Human ecology.; Social ecology.; Écocritique.; Écologie humaine.; Écologie sociale.; human ecology.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Ecocriticism; Human ecology; Anthropocene.; Early Modern.; Exterranean.; Extraction.; Extractivism.; Humanism.; Latour.; Mining.; Posthumanism.; Electronic books.; Electronic book.